Taking Pitch from the Lake to the Wharf, Trinidad, B.W.I. - (:unkn) unknown (D. Adamson, Stationer, Port of Spain, 2010)
Photo of trams transporting pitch from the Pitch Lake to a wharf in Trinidad.
Colour: Black and White ; Style: Landscape ; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Pitch Lake, The; Asphalt industry; Railroads; Trams